Implementasi Model Quantum Teaching melalui Karyawisata terhadap Hasil Belajar Siswa Sekolah Dasar dalam Pembelajaran IPS - Daniar Asyari; Wenny Yolandha; Yona Wahyuningsih (Departement of Mathematics Education, 2023)
The rapid development of the times has led to the emergence of new challenges for the world of education. The government continues to make various efforts to produce quality graduates to face the challenges of the times. Through the policy of implementing a character education curriculum by integrating character values ​​into intra-curricular, co-curricular and extra-curricular activities, this is one of the efforts made by the government through madrasas to realize quality graduates with good character according to national education goals. This study aims to analyze and obtain information regarding the Implementation of the Bandung Mayor's Regulation Number 004 of 2019 regarding the Implementation of the Character Education Curriculum in improving the quality of graduates in Madrasah. This research uses a case study approach. Data collection techniques were carried out by means of observation, interviews, and documentation studies. the character education curriculum has been well prepared by the madrasah by involving all madrasah stakeholders and referring to the vision and mission, 2) implementation of the character education curriculum by integrating character values ​​that have been determined according to the needs of madrasahs through learning, extracurricular, and habituation activities, 3) supervision of the character education curriculum is carried out directly by the head of the madrasa who is assisted by wakamad and teachers continuously either directly or indirectly, and 4) Supporting and inhibiting factors for the character education curriculum come from both internal and external sources. Supporting factors are in the form of cooperation that exists between the madrasah, parents, and the community, as well as moral and material support. While the inhibiting factors, there are still students who violate the rules, busy parents, the influence of social media and the environment